GPS evidence for a coherent Antarctic plate and for postglacial rebound in Marie Byrd Land - Luyendyk, Bruce P. (Pasadena, CA : Jet Propulsion Laboratory, National Aeronautics and Space Administration, 2003., 2005)
GPS measurements collected between 1999 and 2002 in Marie Byrd Land, West Antarctica indicate no significant present motion between East and West Antarctica greater than 1-2 nm/yr. NASA